A Contribution to the Study of Social Inequality in the Late Neolithic of the Central Balkans - Marko Porčić (Etnoantropološki Problemi, 2022)
The social inequality represents one of the major problems of the contemporary world and an important anthropological subject. The transition to agriculture is often viewed as an important turning point for the development of social inequality in (pre)history. For this reason, the study of the social inequality in the Neolithic communities is of particular importance for the understanding of the origins and the development of this phenomenon. This paper represents an empirical contribution to the study of social inequality in the Late Neolithic in the Central Balkans (5300-4500 BCE). The aim is to quanitfy and estimate the levels of inequality between households in three Late Neolithic settlements: Belovode, Pločnik, and Drenovac. In line with the current methods for the estimation of social inequality from archaeological remains, this study relies on the house floor area as a proxy for household wealth. The house floor area measurements are based on the geophysical surveys data published in the literature with around 1000 house floor area measurements available for the analysis. The Gini index is calculated for each site based in the distribution of house floor area. The results suggest that the social inequality on all three sites was relatively low, as the Gini values range from 0.18 to 0.22. These values fit well with the Gini estimates based on the previous research of the social inequality in the Neolithic and Eneolithic period in the Central Balkans. When compared to the cross-cultural variation based on the ethnographic, historical and archaeological sources from the literature, these values are low compared to other horticultural and agricultural communities. One potential explanation for such low values is that the agricultural production in the Late Neolithic of the Central Balkans was labor-limited rather than land-limited, which usually results in the low potential for social inequality, as hypothesized and shown by Bogaard et al. (2019). On the other hand, we must keep in mind that the wealth is measured by proxy which is suitable for the detection of statistical trends in cross-cultural comparisons, but may be less reliable for individual cases. Moreover, it is not certain that the individual house is the basic social unit, as it is possible that the basic social unit for a corporate group which includes extended families living in several houses. Therefore, the result which suggests low levels of social inequality should be taken as a hypothesis which needs to be tested further with other classes of evidence.